Research and Development of Natural Product Tanshinone I: Pharmacology, Total Synthesis, and Structure Modifications - Huang, Xing; Jin, Lili; Deng, Hao; Wu, Dan; Shen, Qing-kun; Quan, Zhe-shan; Zhang, Chang-hao; Guo, Hong-Yan (Frontiers in Pharmacology, 2022)
Salvia miltiorrhiza (S. miltiorrhiza), which has been used for thousands of years to treat cardiovascular diseases, is a well-known Chinese medicinal plant. The fat-soluble tanshinones in S. miltiorrhiza are important biologically active ingredients including tanshinone I, tanshinone IIA, dihydrotanshinone, and cryptotanshinone. Tanshinone I, a natural diterpenoid quinone compound widely used in traditional Chinese medicine, has a wide range of biological effects including anti-cancer, antioxidant, neuroprotective, and anti-inflammatory activities. To further improve its potency, water solubility, and bioavailability, tanshinone I can be used as a platform for drug discovery to generate high-quality drug candidates with unique targets and enhanced drug properties. Numerous derivatives of tanshinone I have been developed and have contributed to major advances in the identification of new drugs to treat human cancers and other diseases and in the study of related molecular mechanisms. This review focuses on the structural modification, total synthesis, and pharmacology of tanshinone I. We hope that this review will help understanding the research progress in this field and provide constructive suggestions for further research on tanshinone I.